Accelerated versus conventional corneal crosslinking for refractive instability: an update. Issue 4 (July 2017) - Kymionis, George D.; Kontadakis, George A.; Hashemi, Kattayoon K.
Abstract : Purpose of review: Corneal crosslinking (CXL) is a relatively new treatment modality offering refractive stability in patients with ectatic disorders. The procedure as initially described (Dresden protocol) is time consuming; accelerated protocols have been lately developed. The purpose of this review is to present the recent findings regarding the comparison of accelerated CXL with the conventional Dresden protocol. Recent findings: A variety of accelerated protocols are described in the literature. Safety and efficacy of the procedures with regard to stability seem to be equivalent in initial studies but indirect measures of efficacy, such as demarcation line depth and laboratory measurements, do not always confirm equivalence of accelerated protocols in comparison to conventional one. Modified accelerated protocols must be developed in order to overcome this. Summary: Accelerated CXL protocols seem to be a valid alternative to the conventional protocol; however, more comparative long term studies are needed to confirm the validity and to elucidate which accelerated protocol is ideal in each case.